Pension Management, Risks and Investment Strategies: A Study of Defined Contributory Pension Scheme in Nigeria (Journal of Management and Social Sciences, 2022)
The decline in defined benefit schemes is necessitated by the perception that defined contribution shifts investment and longevity risks to workers. The plan offers a flexible mechanism for saving for retirement, enabling the enrollees in share of investment returns. The idea of managing risk and establishing dynamic investment strategies in the pension industry cuts across every region of the world as it is critical to the survival and operation of a defined contributory scheme since unprecedented occurrence may exist. The identification and evaluation of actual and potential risk areas as they pertain to pension administration are essential for the termination, transfer, acceptance, or mitigation of each risk. The paper also examines and evaluates whether the relative performance of different investment strategies adopted in the pension scheme is panacea for sustaining it in Nigeria. The methodology applied here is exploratory in nature due to the doubt established by retirees on the adoption of new Contributory Pension Scheme (CPU) in Nigeria as an approach to resolving pension management problems. The paper recommended that a proper institutional design of the pension fund industry and intensive use of market surveillance are efficient tools for dealing with most of the operational risks of funded pension fund schemes in emerging economies.Keywords    Risk management, investment strategies, defined contributory pension scheme, sustainability, Nigeria